Clinical Practice Guidelines by the Infectious Diseases Society of America: 2018 Update on Diagnosis, Treatment, Chemoprophylaxis, and Institutional Outbreak Management of Seasonal Influenza. (19th December 2018) - Uyeki, Timothy M; Bernstein, Henry H; Bradley, John S; Englund, Janet A; File, Thomas M; Fry, Alicia M; Gravenstein, Stefan; Hayden, Frederick G; Harper, Scott A; Hirshon, Jon Mark; Ison, Michael G; Johnston, B Lynn; et al.
Abstract: These clinical practice guidelines are an update of the guidelines published by the Infectious Diseases Society of America (IDSA) in 2009, prior to the 2009 H1N1 influenza pandemic. This document addresses new information regarding diagnostic testing, treatment and chemoprophylaxis with antiviral medications, and issues related to institutional outbreak management for seasonal influenza. It is intended for use by primary care clinicians, obstetricians, emergency medicine providers, hospitalists, laboratorians, and infectious disease specialists, as well as other clinicians managing patients with suspected or laboratory-confirmed influenza. The guidelines consider the care of children and adults, including special populations such as pregnant and postpartum women and immunocompromised patients.